ANASE: Lessons from 'Unreliable Findings' - Brooker, Peter (Cranfield University, 2008)
In late 2007, the ANASE (Attitudes to Noise from Aviation Sources in England) report was published. It claimed that people are increasingly annoyed by aircraft noise, and it estimated how much they would be willing to pay to get rid of it. But its quantitative ‘findings were rejected as unreliable by the Department for Transport’ (BBC website). The project’s managers were warned in its early stages that the work would fail to deliver good value for money and not meet accepted technical/statistical standards. How and why did it fail? What were the methodological and project management failings? What are the lessons for acoustics professionals?